Preventive Effect of Antioxidative Nutrient‐Rich Enteral Diet Against Liver Ischemia and Reperfusion Injury. Issue 1 (5th June 2018) - Miyauchi, Tomoyuki; Uchida, Yoichiro; Kadono, Kentaro; Hirao, Hirofumi; Kawasoe, Junya; Watanabe, Takeshi; Ueda, Shugo; Jobara, Kanta; Kaido, Toshimi; Okajima, Hideaki; Terajima, Hiroaki; Uemoto, Shinji
Abstract: Background: Liver ischemia and reperfusion injury (IRI) is a major problem associated with liver surgery. This study is aimed to compare the preventive effect of an antioxidative nutrient‐rich enteral diet (Ao diet) with an ordinal enteral diet (control diet) against liver IRI. Methods: The Ao diet was an ordinary diet comprising polyphenols (catechin and proanthocyanidin) and enhanced levels of vitamins C and E. Male C57BL/6 mice were fed the Ao or control diet for 7 days before ischemic insult for 60 minutes, followed by reperfusion for 6 hours. The levels of inflammatory cytokines, chemokines, and antioxidant enzymes and oxidative stress were evaluated. Results: After 7 days of pretreatment with the Ao diet, the serum levels of vitamins C and E in mice were markedly elevated. The levels of serum aspartate aminotransferase and alanine aminotransferase, as well as the scores of liver necrosis caused by ischemia and reperfusion, were significantly lower in the Ao diet group than in the control diet group. The gene expression levels of inflammatory cytokines and chemokines, such as interleukin‐6 and CXCL1, were significantly lower in the Ao diet group. In the liver, the levels of antioxidant enzymes superoxide dismutase 1 (SOD1) and SOD2 were significantly higher and the malondialdehyde levels were significantly lower in the Ao diet group. Cell adhesion molecule expression was significantly lower, and neutrophil and macrophage infiltration was less in the Ao diet group. Conclusions: Antioxidative nutrient supplementation to an ordinary enteral diet may mitigate liver IRI by causing an antioxidant effect and suppressing inflammation.